2009
DOI: 10.1186/1471-2431-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about childhood autism and opinion among healthcare workers on availability of facilities and law caring for the needs and rights of children with childhood autism and other developmental disorders in Nigeria

Abstract: Background: In designing programs to raise the community level of awareness about childhood autism in sub-Saharan Africa, it is logical to use the primary healthcare workers as contact point for education of the general public. Tertiary healthcare workers could play the role of trainers on childhood autism at primary healthcare level. Assessing their baseline knowledge about childhood autism to detect areas of knowledge gap is an essential ingredient in starting off such programs that would be aimed at early d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
5
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 17 publications
8
84
5
1
Order By: Relevance
“…Studies have been conducted on how ASD is understood by Nigerian healthcare professionals such as doctors (Eseigbe et al, 2015), nurses (Igwe et al, 2011), healthcare workers (Bakare et al, 2008;Bakare et al, 2009aBakare et al, , 2009b and medical students (Igwe et al, 2010). All the studies have identified knowledge about ASD to be low and have highlighted a need for education and training.…”
Section: Teachers' Knowledge Regarding Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted on how ASD is understood by Nigerian healthcare professionals such as doctors (Eseigbe et al, 2015), nurses (Igwe et al, 2011), healthcare workers (Bakare et al, 2008;Bakare et al, 2009aBakare et al, , 2009b and medical students (Igwe et al, 2010). All the studies have identified knowledge about ASD to be low and have highlighted a need for education and training.…”
Section: Teachers' Knowledge Regarding Asdmentioning
confidence: 99%
“…This tool was designed specifically to identify knowledge about ASD within a Nigerian context. It has been validated and used in multiple studies relating to Nigerian healthcare professionals' knowledge regarding ASD (Bakare et al, 2008(Bakare et al, , 2009bIgwe et al, 2010Igwe et al, , 2011. The tool collects data in four domains.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Using the template of findings and observations made during the ANPPCAN's study, a standard questionnaire for assessing knowledge of health care workers about autism spectrum disorders, aimed at early recognition was designed and validated (Bakare et al, 2008). Subsequent study done following ANPPCAN survey consistently was showing the same trend of low level of knowledge and awareness about autism spectrum disorders among the healthcare workers (Bakare et al, 2009b). It was further established that the ability of healthcare workers working in psychiatric facilities to recognize symptoms of autism spectrum disorder was better than their counterparts working in pediatric units/departments (Bakare et al, 2009b).…”
Section: Knowledge and Awareness About Autism Spectrum Disorders In Amentioning
confidence: 99%
“…Subsequent study done following ANPPCAN survey consistently was showing the same trend of low level of knowledge and awareness about autism spectrum disorders among the healthcare workers (Bakare et al, 2009b). It was further established that the ability of healthcare workers working in psychiatric facilities to recognize symptoms of autism spectrum disorder was better than their counterparts working in pediatric units/departments (Bakare et al, 2009b). Igwe et al (2010) examined level of knowledge about autism spectrum disorders among potential health care workers presently undergoing their training; they compared final year medical, nursing and psychology students of University of Nigeria in Enugu State, south-eastern Nigeria.…”
Section: Knowledge and Awareness About Autism Spectrum Disorders In Amentioning
confidence: 99%
See 1 more Smart Citation